Jung and educational theory - Semetsky, Inna, 1948-; Wiley InterScience (Online service) (Hoboken : John Wiley & Sons, 2012)
Jung and Educational Theory offers a new take on Jung's work, providing original, rich and informative material on his impact on educational research. Explores Jung's writing from the standpoint of educational philosophy, assessing what it has to offer to theories of education. Highlights Jung's emphasis on education's role in bringing up integrated and ethical human beings. Offers the perspectives of a diversity of academics and practitioners, on topics ranging from the role of the unconscious in learning to the polytheistic classroom.
Front Matter -- Jung and the Soul of Education (at the 'Crunch') / Susan Rowland -- On the 'Art and Science' of Personal Transformation: Some critical reflections / Raya A Jones -- The Polytheistic Classroom / Bernie Neville -- Itinerary of the Knower : Mapping the ways of gnosis, Sophia, and imaginative education / Antonina Lukenchuk -- The Unifying Function of Affect: Founding a theory of psychocultural development in the epistemology of John Dewey and Carl Jung / Peter T. Dunlap -- Deleuze's Philosophy and Jung's Psychology: Learning and the Unconscious / Inna Semetsky, Joshua Ramey -- 'The Other Half' of Educat.ion: Unconscious education of children / Shiho Main -- Complex Education: Depth psychology as a mode of ethical pedagogy / Robert Romanyshyn -- Jung and Tarot: A Theory-practice Nexus in Education and Counselling / Inna Semetsky -- Index.
Included bibliographical references and index.
Print version record.
Keywords: Jung, C. G. -- 1875-1961 -- Influence; Jung, C. G. -- 1875-1961.; Education -- Philosophy; Educational psychology; Psychoanalysis and education; Education; Education -- Philosophy; Educational psychology; Influence (Literary, artistic, etc.); Psychoanalysis and education; Electronic books